The end of money and the future of civilization - Greco, Thomas H., 1936- (White River Junction, Vt. : Chelsea Green Pub., 2009)
The subject of money, banking and finance is being demystified by tracing historical landmarks and important evolutionary shifts that have changed the essential nature of money. This book cuts to the very core of the global financial trouble and points toward several pathways that might allow us to slowly climb out of it. He also provides specific proposals and exchange-system architectures for local, regional, national and global financial systems. It offers innovative strategies for their implementation and ouline actions that grassroots organizations, business, and governments will need to take to achieve success.
Includes bibliographical references (p. [257]-260) and index.
nmn 14/05/13
Loans
Keywords: Money -- History; Banks and banking -- History; Finance -- History; Power (Social sciences) -- History